Trial of the sun queen eaudiobook - J Tuli, Nisha (Artefacts of Ouranos, 2023)
The Bachelor meets The Hunger Games. Ten women. A deadly contest. Only one can win the Sun King's heart. Lor has endured twelve long years of torment under the Aurora King's rule. Her only desire is to get free and pay him back for every moment of misery she's endured. When a surprise release finds her in the hands of the Sun King, Lor is thrust into the spotlight as she competes against nine other tributes for the role of queen. If she wins his heart, she'll earn her freedom and finally get her revenge. But Lor doesn't belong in the Sun Queen trials. Not only does she not understand why she was freed, she isn't a citizen of the Sun King's court. The other tributes resent her presence and will stop at nothing to ensure Lor is wiped off the gameboard—permanently. Now Lor must win because if she loses, she dies. Or worse, she'll be sent back into the hands of the Aurora King. This glittering fae romance is perfect for fans of Sarah J. Maas, Jennifer Armentrout, and Raven Kennedy. Trial of the Sun Queen is the first book in the Artefacts of Ouranos series with an eventual happy ever after.